2014
DOI: 10.1093/ntr/ntu182
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Chronic Moderate Exercise in Smoke Exposed or Nicotine Applied Rats From Acute Stress

Abstract: Biochemical parameters and histological scoring indicated increased tissue injury due to nicotine application and cigarette smoke exposure and exercise training ameliorated these effects in most of the tissues of acute stress induced rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Clinical trials have indicated that chronic physical exercise can have antidepressant and anxiolytic effects [21][22][23]. Furthermore, moderate intensity exercise also reduces oxidative stress [24,25], implying that exercise can be an effective and cost-efficient therapeutic alternative for a variety of anxiety and mood-related disorders. Although exercise has been shown as a therapeutic tool in most of the studies, nonvoluntary chronic exercise may be a stressor due to experimental design, housing or testing environment, rearing and handling situations in animal studies [26].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have indicated that chronic physical exercise can have antidepressant and anxiolytic effects [21][22][23]. Furthermore, moderate intensity exercise also reduces oxidative stress [24,25], implying that exercise can be an effective and cost-efficient therapeutic alternative for a variety of anxiety and mood-related disorders. Although exercise has been shown as a therapeutic tool in most of the studies, nonvoluntary chronic exercise may be a stressor due to experimental design, housing or testing environment, rearing and handling situations in animal studies [26].…”
Section: Introductionmentioning
confidence: 99%
“…24 It has been reported that the amount of lipid peroxidation depends on the intensity, duration and mode of exercise. For example, a short-term of high-intensity exercise can increase speed of lipid peroxidation which caused by oxidative stress, 25 - 27 while long period exercise can diminish lipid peroxidation process and prevents tissue from damaging. 28 , 29 The discrepancies between the present findings and those of other results could be related to the duration, intensity and mode of exercise used during this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Each time six rats were placed in the in the mechanical smoking box and exposed to four cigarettes at 15‐minute intervals. The procedure was applied 6 days a week, for 5 weeks …”
Section: Methodsmentioning
confidence: 99%